One-pot sonochemical synthesis of reduced graphene oxide uniformly decorated with ultrafine silver nanoparticles for non-enzymatic detection of H2O2 and optical detection of mercury ions - Golsheikh, Amir Moradi; Huang, Nay Ming; Lim, Hong Ngee; Zakaria, Rozalina (Royal Society of Chemistry, 2014)

(untitled)
Reduced graphene oxide (rGO) uniformly decorated with silver nanoparticles (AgNPs) was synthesized through the simple ultrasonic irradiation of an aqueous solution containing a silver ammonia complex (Ag(NH3)2OH) and graphene oxide (GO). The results of X-ray diffraction, Fourier-transform infrared transmission spectroscopy, X-ray photoelectron spectroscopy and Raman spectroscopy confirmed the simultaneous formation of cubic-phase AgNPs and the reduction of GO through an ultrasonication process. The size of the nanoparticles could be tuned by adjusting the volume ratio of the precursors and the ultrasonic irradiation time. Transmission electron microscopy images showed a uniform distribution of ultrafine spherical AgNPs with a narrow size distribution on the rGO sheets, which could only be achieved using the silver ammonia complex, rather than silver nitrate, as the precursor. The average particle size of the silver with the narrowest size distribution was 4.57 nm. The prepared AgNPs–rGO modified glassy carbon electrode exhibited notable electrocatalytic activity toward the non-enzymatic detection of H2O2 with a wide linear range of 0.1–70 mM (R2 = 0.9984) and a detection limit of 4.3 μM. Furthermore, the prepared AgNPs–rGO composite was employed for the spectral detection of Hg2+ ions and showed a detection limit of 20 nM.